Metamaterial-based strain sensors - Jining Li; Withawat Withayachumnankul; Shengjiang Chang; Derek Abbott (My University, 2011)
In this paper, two metamaterial-based strain sensors at terahertz frequencies are introduced and simulated using CST Microwave Studio. They exhibit a large shift in the resonance frequency upon stretching or compression. They are very well suitable to monitoring and detecting mechanical deformation of a target structure remotely.
Keywords: Strain (injury); Metamaterials and Metasurfaces Applications